Efficacy of Traditional Chinese Medicine Tonifying Kidney (Bushen) and Activating Blood (Huoxue) Prescription for Premature Ovarian Insufficiency: A Systematic Review and Meta-Analysis. (21st April 2020) - Li, Hui-Fang; Shen, Qi-Hong; Chen, Wen-Jun; Chen, Wei-Min; Feng, Zhang-Feng; Yu, Li-Ying
Abstract : Context . Premature ovarian insufficiency (POI) is one of the difficult gynecological diseases with complex etiologies. Tonifying kidney (bushen) and activating blood (huoxue) prescription (TKABP) is a popular traditional Chinese medicine (TCM) therapy which is commonly applied for POI. However, its efficacy and safety are still controversial. Objective . We carried out this systematic review and meta-analysis to evaluate the effectiveness of TKABP on POI. Methods . The following eight databases were searched from the establishment to September 30, 2019, for randomized controlled trials (RCTs): PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), the Chinese BioMedical database (CBM), Chinese Scientific Journal Database (VIP), and the Wanfang database. The quality of evidence was estimated by the Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Results . Twenty-three RCTs involving 1712 patients with POI were included. Compared to hormone therapy (HT) groups, TKABP groups showed a significantly higher total effective rate (RR: 1.10; 95% CI: 1.04–1.17; P < 0.01, I 2  = 32%). In addition, TKABP groups revealed a better improvement in terms of serum follicle-stimulating hormone (FSH) levels, serum estradiol (E2 ) levels, peak systolic velocity (PSV) of ovarian stromal blood, and Kupperman index (KI) score. However, serum luteinizing hormone (LH) levels and ovarian volume (OV) showed no significant statistical difference. Subgroup analyses showed that herbal paste and 3 months of treatment duration had a greater effect on the improvement of hormone levels. Besides, the occurrence of related adverse events in TKABP groups was lower than that in HT groups. Conclusions . Our review suggests that TKABP appears to be an effective and safe measure for patients with POI, and the herbal paste may be superior. However, the methodological quality of included RCTs was unsatisfactory, and it is necessary to verify its effectiveness with furthermore standardized researches of rigorous design.